Proposal and assessment of a solid oxide fuel cell cogeneration system in order to produce high-temperature steam aiming at industrial applications. (25th February 2023) - Zhao, Yongming; Xue, Huaqing; Jiang, Luyang; Jin, Xu; Fu, Honghao; Xie, Xiaofang
Abstract: The feature of operating at high temperature enables solid oxide fuel cell (SOFC) generating power at impressive efficiency while providing useful heat. Commercial SOFC cogeneration products for domestic hot water supply are already available, however, the potential of supplying high-temperature heat (especially in the form of steam) for industrial applications has not been well exploited yet. Here, a new SOFC cogeneration system layout is proposed and studied to address the problem. The core idea is to utilize the residual heat in parallel by the method of splitting the high-temperature streams, rather than in cascade as in traditional layouts. Therefore, the application of SOFC cogeneration can be expanded from providing low-temperature heat to high-temperature heat, from homes to industries. The simulation result shows that the layout with anode gas recycle (AGR) has the best performance in both net and cogeneration efficiency. The best predicted net efficiency is 56.9% and cogeneration efficiency 86.8% for the AGR layout. For the AGR layout with a net capacity of 10   MW, the steam production ability of medium, low and super low pressures are 5903   kg / h, 6436   kg / h and 6748   kg / h, respectively. The investigated gas split locations only have negligible effect on the steam production ability. Highlights: Method of supplying high-temperature waste heat is proposed for SOFC cogeneration. Application scope of SOFC cogeneration is expanded from homes to industries. Three different SOFC cogeneration system layouts are investigated and compared. Net efficiency, cogeneration efficiency and steam production ability are evaluated.